The Anti-Cancer, Anti-Inflammatory, Antibacterial, Antifungal, Anti-Oxidant and Phytochemical Investigation of Flowers and Stems of Anacyclus Clavatus Plant Extracts - Hamad Hasan; Salma Jadallah; Zuhir Akrim; Fatma Ali; Mooada Saber (AlQalam Journal of Medical and Applied Sciences, 2025)
The alternative medications have been used in Libya for many years. Libya is considered rich in medicinal plants. Thousands of these plants grow naturally throughout the country, particularly in the Al-Jabal Al-Akhtar region. This study aims to estimate the antioxidant activity, phytochemical screening, total phenols contents, antibacterial, anti-inflammatory, and anti-cancer investigations of the flowers and steams of Anacyclus Clavatus extracts. Two different extracts were applied in this study (Aqueous and Alcohol). The results showed the presence of some active natural compounds as carbohydrates and/or glycosides, sterols and/or triterpenes, tannins, flavonoids, and cardiac glycosides in all studied plant species with different amounts. The total phenols and antioxidant activity contents were 9.1 and 11.40 ppm for stems and flowers, respectively. On the other side, the contents of antioxidants were 3.26 and 3.93 ppm in stems and flowers of the studied extracts. The antibacterial and antifungal applications showed that the extracts gave inhibition activities on the selected bacteria species of (Staph and Klebsiella) and fungi species of (Aspergilluis and Penicillium). For the anti-inflammatory investigation. The extracts of flowers and stems gave indicating that the compound with less Hemolysis Inhibition % results in good inhibitory activity. The anti-cancer activities of the plant extracts were applied on Cancer cell lines (HePG2). The plant extract was shown to have potential antitumor action against cell lines. The cytotoxicity of the plant extract was tested using human Liver (HepG 2) cell lines. تم استخدام الطب البديل بالأعشاب في ليبيا منذ العديد من السنوات السابقة بليبيا وذلك لكونها تعتبر من الاكثر المناطق احتواء عللا النباتات الطبية وخصوصا بمنطقة الجبل الاخضر بليبيا ، وتهدف هذه الدراسة الي تحديد محتويات كلا من مضادات الأكسدة والمحتوى الكلي من المركبات الفينولية وكذلك الفحص الفيتو كيميائي ومدى فعالية مضادات البكتريا والفطريات والالتهابات والخلايا السرطانية لمستخلصات سيقان وزهور نبات القريصة النامية في الجبل الاخضر. وقد بينت نتائج هه الدراسة وجود العديد من المركبات الطبيعية الهامة مثل الكربوهيدرات او الجليكوسيدات والسيترولات او التربينات والتانينات والفلافونيدات في مستخلصات النبات قيد الدراسة. وكانت تراكيز المركبات الفينولية الكلية 9.1 و 11.40 جزء من المليون ، بينما كانت محتويات مضادات الاكسدة 3.93 , 3.26 جزء من المليون ، و ذلك لمستخلصات السيقان والاوراق على التوالي. كما بينت نتائج هذه الدراسة ان المستخلصات اعطت تأثيرا مثبظا على انواع البكتريا المستخدمة في هذه الدراسة وهي (Klebsiell (Staph and والفطريات (Aspergilluis and Penicillium) ، وكذلك اعطت تأثيرا مثبطا على الالتهابات ، وتم استخدام المستخلصات كمضادات للخلايا السرطانية على خلايا سرطان الكبد وبينت النتائج ان هناك تأثيرات عالية عليها